Towards direct analysis of solid and liquid samples exploiting a 3D printed dialysis unit and sequential injection: Application for automated derivatization and determination of gamma-aminobutyric acid in foodstuff and beverages - Kasetsoontorn, Bhoonnarasa; Choengchan, Nathawut (My University, 2020)
In this work, a new design of a dialysis unit for direct analysis of solid and liquid samples is presented. The homemade unit was constructed using a 3D printer due to its simple and fast fabrication ability. The dialysis unit is composed of cylindrical-shaped donor and acceptor chambers. A stainless steel sieve is installed inside the donor chamber. SEM images clearly showed that the sieve prevented membrane blockage by suspension particles in the sample. Multiple dialysis units were connected to a sequential injection (SI) system for serial determination of gamma-aminobutyric acid (GABA) in solid and liquid samples. The dialysate from each dialysis unit was consecutively aspirated into the SI flow line for on-line derivatization of GABA with 2-hydroxy-1-naphthaldehyde (3.0% w/v). The derivative was detected spectrophotometrically at 425 nm. The linear calibration range extended to 1000 mg L−1 GABA (r2 > 0.99) with high precision (1.2 %RSD). The developed system was applied to analysis of dietary supplements, grains of germinated brown rice and milk. The samples were directly introduced into the donor chamber either as powder or liquids. The measured GABA content using the developed method was compared using high performance liquid chromatography, with good agreement using Pearson's correlation (r2 = 0.9999). The method has high accuracy based on recovery studies (99.8 ± 1.5%) and high sample throughput (64 samples h−1).
Keywords: 3D printing; Automated derivatization; Dialysis; Direct analysis; GABA; Sequential injection